Implementasi Solusi Kreatif dalam Meningkatkan Budaya Literasi Pembelajaran PAI (Studi di MTs Mathlaul Khaer Cintapada Kota Tasikmalaya) - Yanto Maulana Restu; Hana Rosidah; Mochammad Jalalul Bulqini Firdaus; Muhammad Ilyas Ramdhan; Ripan Maulana (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the implementation of creative solutions in improving the literacy culture of Islamic Education (PAI) learning. This research is motivated by the challenge of a low religious literacy culture among students, which prompted the Headmaster of MTs Mathlaul Khaer Cintapada to establish the Integrated Tahfidz Program in 2022. This study uses a qualitative approach with a descriptive type. The creative solution implemented is a combination of direct memorization deposits (setoran) and the utilization of the Al-Kalam digital application, which facilitates students in memorizing, understanding Tajwid, and Makharijul Huruf. The memorization target over three years is 6 Juz (1, 2, 27, 28, 29, 30), with a success rate reaching 70% of students. The results show that this program has successfully increased student enthusiasm and literacy, marked by the annual Tahfidz Graduation as a form of appreciation and motivation. This study concludes that the integration of digital technology and structured programs effectively strengthens religious literacy in schools.   Keywords: Islamic Education Learning, PAI Learning, Religious Literacy Culture, Integrated Tahfidz Program, Creative Solutions.